Assessment of the effect of hemostatic materials on blood calcium concentration - V. A. Lipatov; S. V. Lazarenko; D. A. Severinov (Исследования и практика в медицине, 2021)
Purpose of the study. Assessment of the effect of hemostatic materials on concentration of calcium of blood.Materials and methods. The following groups of local hemostatic materials were studied: collagen plate (No. 2), hemostatic sponge from medical gelatin (No. 3), oxidized cellulose material (No. 4), experimental samples of hemostatic sponge developed by the team of authors, based on the sodium salt of carboxymethylcellulose with various modifications (groups No. 5-8). In the control group (No. 1), only blood of volunteer donors was used, without introducing the test materials. Evaluation of the effect of hemostatic materials on blood calcium concentration was carried out according to the described method: «Method for comparative investigation of the effectiveness of local hemostatic agents in an in vitro experiment» Russian patent No. 2709 517. According to the results of the study, median, 25 and 75 percentiles were calculated. The validity of differences between groups was determined using the non-parametric Mann-Whitney test (p<0.05).Results. In groups using various materials, such as group No. 2 (Tachocomb) by 0.24 mmol/L and group № 4 (Surgicel Fibrillar) by 0.7 mmol/L, the serum calcium level was statistically significantly lower than the control group. Significant differences of calcium level values after blood immersion of volunteer donor samples based on cellulose derivatives were revealed, namely in group No. 5 (Na-CMC + Tranexamic acid pressed) value exceeds that in group No. 4 by 0.58 mmol/l. In other cases, comparisons of calcium concentration values in groups using experimental samples (not introduced into clinical practice) with material widely used in abdominal surgery (group No. 4) were found to be greater: in group No. 6 (Na-CMC + Tranexamic acid unsaturated) by 0.61 mmol/l, in group No. 7 (Na-CMC pressed) by 0.75 mmol/l, in group No. 8 (Na-CMC unsaturated) by 0.5 mmol/l.Conclusion. It should be noted that although there are no significant differences in the groups using experimental samples of local hemostatic agents and the control group, the calcium levels in groups No. 5-6 are close to those in the groups using widely known materials such as Tachocomb (No. 2) and Gelita-Spon Standart (No. 3). Also, among the samples developed by the authors, the greatest effectiveness was identified in group No. 8 (Na-CMC, unpressed), in which the serum calcium levels (2.14 mmol/L) are lower than in groups No. 5-7.